PREDICTION ON OPTIMISTIC AND MOTIVATION FACTOR TO RELAPSE AMONG FORMER DRUG ABUSE - Razali, Asbah; Ani, Fauziah; Tohar, Siti nor Azhani Mohd (International Journal of Psychosocial Rehabilitation, 2020)
The objective of this study is to identify predictors (optimistic and motivation) that correspond to relapse among former drug abuse in Malaysia. This study involves 50 former drug abuse who completed their questionnaire treatment and rehabilitation period and utilises three instruments, the Relapse Motivation Questionnaire (RMQ), Optimism used Life Orientation Test (LOT) and relaps was using the Inventory of Drug- Taking Situations (IDTS). This study uses descriptive statistical method or frequency to see the percentage for the demographic factor, while the inferential statistical method such as the Pearson correlation and multiple linear regression were used to test the research question. Results showed that there is not any correlation between relapse towards drug addiction and optimism is (r=-0.261, p-value=.067) while there is significant correlation between relapse towards drug addiction and motivational (r= -.387**, p-value=.006) as well as motivational and optimism (r= .536**, p-value=.000). This relationship between motivational and relapse is negative between motivational and relapse while positive between motivational and optimism, which indicates that as the motivational increase the chances of relapse towards drug addiction decrease while on the other hand if motivational increase then optimism increase. Multiple regression analysis indicated that a both the variables statistically not significant and didn’t predict F (3, 46) = 57.208, p-value < .005, R2 = .789. So, without optimism, motivational behavior and strong cooperation among human beings it would be complicated to help former addicts to re-start their lives as common human beings this country.